An analysis of the comic Christ figure in three twentieth-century American novels - Falgui, Raymond G.
This study analyzes the phenomenon of the "comic Christ figure" in twentieth-century American literature. The Christ figure is a fictional character that is compared to or associated with the religious and historical figure of Jesus Christ. Numerous examples of the Christ figure are found in literature, but this study focuses on Christ figures whose characterizations exhibit comic or humorous elements -- qualities that are seen as inimical or contrary to the sacred aspects of the Christ figure. Thus, the comic Christ figure represents a fusion of opposing or contradictory elements, and this study will analyze the reasons for, as well as the implications of, such a volatile union. The specific subjects of this study are three comic Christ figures from 20th-century American literature: Jim Casy from John Steinbeck's The Grapes of Wrath, Randle P. McMurphy from One Flew Over The Cuckoo's Nest, and Owen Meany form A Prayer For Owen Meany. This study asserts that that the appearance of these comic Christ figures is tied to the ongoing "culture war" in the United States - a conflict pitting conservative and religious sectors of American society against their more liberal or secular countrymen. This study asserts that the chosen comic Christ figures represent an attempt to challenge or undermine the divisions created by this conflict. The chosen characters utilize comedy and humor in the fulfillment of the Christ figure's traditional roles of savior and sacrificial scapegoat; the comic and humorous are thereby integrated into the Christ figure's identity and mission. This successful union of contradictory elements, in turn, holds the prevailing attitudes of both sides of the aforementioned cultural conflict up to comic ridicule and scrutiny -- exposing their respective shortcomings and prejudices, and emphasizing the need for American culture and society to move beyond existing binary modes of thought and ideology.